Mechanical characteristics and freezing-thawing degradation mechanism for mortar samples under sodium sulfate solutions attack - Han, Tielin; Li, Zhihui (Arabian journal of geosciences, 2021)
The durability of mortar in actual environment is a basic research subject in the current concrete engineering field, and the research on freezing-thawing characteristics of mortar has become one of its important topics. In this paper, physical-mechanical proprieties and freezing-thawing damage mechanisms of mortar samples were carried out under frost action. Meanwhile, ions concentrations (Ca 2+ and Mg 2+ ) dissolved in sodium sulfate solutions were also monitored during the freezing-thawing cycle. The test results showed that physical-mechanical proprieties of mortar samples had a significant trend of gradual deterioration under the action of chemical solutions. Compared with sound mortar, cohesion for mortar samples after 60 freeze-thawing cycles decreased by 37.1%, 26.8%, and 20.9%, when samples soaked in pH=3.0 of Na 2 SO 4 , pH=12.0 of NaOH, and pH=7.0 of Na 2 SO 4 solutions, respectively, and internal friction angle decreased by 18.4%, 14.2%, and 7.3%, respectively. This indicated that the degree of damage to the cohesion of samples was greater than that of the internal friction angle. Uniaxial compressive strength of mortar samples has a linear relationship with the damage variable, and peak axial strain has an exponential relationship with the damage variable. Meanwhile, the degree of freezing-thawing deterioration was quantitatively analyzed based on changes in porosity of the samples. There were obvious relationships between ions concentrations and physical-mechanical proprieties. And the correlations relationships among the damage variables, physical-mechanical proprieties of mortar, and Ca 2+ and Mg 2+ ion concentrations are indirectly obtained, that is, the degradation law of physical-mechanical proprieties of mortar is influenced by damage variables and Ca 2+ and Mg 2+ ion concentrations.